Temporal and topographical changes in theta power between middle childhood and adolescence during sentence comprehension. (February 2022) - Maguire, Mandy J.; Schneider, Julie M.; Melamed, Tina C.; Ralph, Yvonne K.; Poudel, Sonali; Raval, Vyom M.; Mikhail, David; Abel, Alyson D.
Abstract: Time frequency analysis of the EEG is increasingly used to study the neural oscillations supporting language comprehension. Although this method holds promise for developmental research, most existing work focuses on adults. Theta power (4–8 Hz) in particular often corresponds to semantic processing of words in isolation and in ongoing text. Here we investigated how the timing and topography of theta engagement to individual words during written sentence processing changes between childhood and adolescence (8–15 years). Results show that topographically, the theta response is broadly distributed in children, occurring over left and right central-posterior and midline frontal areas, and localizes to left central-posterior areas by adolescence. There were two notable developmental shifts. First, in response to each word, early (150–300 msec) theta engagement over frontal areas significantly decreases between 8 and 9 years and 10–11 years. Second, throughout the sentence, theta engagement over the right parietal areas significantly decreases between 10 and 11 years and 12–13 years with younger children's theta response remaining significantly elevated between words compared to adolescents'. We found no significant differences between 12 and 13 years and 14–15 years. These findings indicate that children's engagement of the language network during sentence processing continues to change through middle childhood but stabilizes into adolescence.